IMP-68, a Novel IMP-Type Metallo-β-Lactamase in Imipenem-Susceptible Klebsiella pneumoniae - Hiroaki Kubota (American Society for Microbiology, 2019)
ABSTRACT We recently detected a novel variant of an IMP-type metallo-β-lactamase gene (blaIMP-68) from meropenem-resistant but imipenem-susceptible Klebsiella pneumoniae TA6363 isolated in Tokyo, Japan. blaIMP-68 encodes a Ser262Gly point mutant of IMP-11, and transformation experiments showed that blaIMP-68 increased the MIC of carbapenems in recipient strains, whereas the MIC of imipenem was not greatly increased relative to that of other carbapenems, including meropenem. Kinetics experiments showed that IMP-68 imipenem-hydrolyzing activity was lower than that for other carbapenems, suggesting that the antimicrobial susceptibility profile of TA6363 originated from IMP-68 substrate specificity. Whole-genome sequencing showed that blaIMP-68 is harbored by the class 1 integron located on the IncL/M plasmid pTMTA63632 (88,953 bp), which was transferable via conjugation. The presence of plasmid-borne blaIMP-68 is notable, because it conferred antimicrobial resistance to carbapenems, except for imipenem, on Enterobacteriaceae and will likely affect treatment plans using antibacterial agents in clinical settings. IMPORTANCE IMP-type metallo-β-lactamases comprise one group of the “Big 5” carbapenemases. Here, a novel blaIMP-68 gene encoding IMP-68 (harboring a Ser262Gly point mutant of IMP-11) was discovered from meropenem-resistant but imipenem-susceptible Klebsiella pneumoniae TA6363. The Ser262Gly substitution was previously identified as important for substrate specificity according to a study of other IMP variants, including IMP-6. We confirmed that IMP-68 exhibited weaker imipenem-hydrolyzing activity than that for other carbapenems, demonstrating that the antimicrobial susceptibility profile of TA6363 originated from IMP-68 substrate specificity, with this likely to affect treatment strategies using antibacterial agents in clinical settings. Notably, the carbapenem resistance conferred by IMP-68 was undetectable based on the MIC of imipenem as a carbapenem representative, which demonstrates a comparable antimicrobial susceptibility profile to IMP-6-producing Enterobacteriaceae that previously spread in Japan due to lack of awareness of its existence.